A full-scale innovative GFRP-concrete hybrid footbridge : description and testing - Sena-Cruz, José (2014)
The present paper describes the construction process of a full-scale innovative GFRP-concrete hybrid footbridge, and summarizes the main tests performed. This footbridge is 11 m long, 2 m wide, simply supported, and composed of two pultruded I-shaped GFRP girders (0.2 m x 0.4 m) and a 0.04 thick deck in steel fiber reinforced self-compacting concrete (SFRSCC). To evaluate the static and dynamic behavior of this footbridge, short and long-term load tests, and dynamic tests were performed.